Assessment of different methods for characterization and simulation of post-cracking behavior of self-compacting steel fiber reinforced concrete - Soltanzadeh, Fatemeh (2019)
The post-cracking tensile properties of steel fiber reinforced concrete (SFRC) is one of the most important aspects that should be considered in design of SFRC structural members. The parameters that describe the post-cracking behavior of SFRC in tension are often derived using indirect methods combined with inverse analysis techniques applied to the results obtained from three- or four-point prism bending tests or from determinate round panel tests. However, there is still some uncertainty regarding the most reliable methodology for evaluating the post-cracking behavior of SFRC. In the present study a steel fiber reinforced self-compacting concrete (SFRSCC) was developed and its post-cracking behavior was investigated through an extensive experimental program composed of small determinate round panel and prism bending tests. Based on the results obtained from this experimental program, the constitutive tensile laws of the developed SFRSCC were obtained indirectly using two numerical approaches, as well as three available analytical approaches based on standards for estimating the stress versus crack width relationship (). The predictive performance of both the numerical and analytical approaches employed for estimating the relationship of the SFRSCC was assessed. The numerical simulations have provided a good prediction of the post-cracking behavior of the concrete. All the analytical formulations also demonstrated an acceptable accuracy for design purposes. Anyhow, among all the employed approaches, the one that considers the results of small determinate round panel tests (rather than that of prism bending tests) has predicted more accurately the constitutive tensile laws of the SFRSCC